STRUCTURE OF FUTURE READYNESS FOREIGN LANGUAGE TEACHERS TO PERSONAL ORIENTED LEARNING OF SENIOR STUDENTS - O.V. Hladka (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the structure of the readiness of future teachers of the foreign language for personality-oriented teaching of high school students. The role of each component in the formation of this phenomenon is revealed.